Physical demands of elite male and female 3 × 3 international basketball matches - Ferioli, D.; Conte, D.; Rucco, D.; Alcaraz, P. E.; Vaquera, A.; Romagnoli, M.; Rampinini, E. (The Journal of Strength and Conditioning Research, 2023)
This study aimed to (1) characterize the physical demands of 3 × 3 basketball games during live playing time and ball possession and (2) assess the differences in physical demands between male and female players. Following an observational design, video footage from 27 games of the International Basketball Federation 3 × 3 World Cup 2019 were analyzed from 104 international 3 × 3 basketball players (n = 52 male and n = 52 female players) resulting in a total of 216 (104 male and 112 female) individual game samples. Manual frame-by-frame time-motion analyses determined the relative frequency (n·min-1) and duration (%) for several physical demands at different intensities, according to sex, during the live playing time and in ball possession phases. Linear mixed models for repeated measures and effect size (ES) analyses revealed small non-significant differences in the intermittent profile of 3 × 3 basketball games according to sex (total movements per minute, male = 39.3 (38.6-40.1); female = 40.2 (39.5-41.0), estimated marginal means with 95% confidence intervals). Female competitions had significantly greater number of low-intensity activities (LIA, small ES) and high-intensity activities (HIA, small ES) performed per minute over longer games (small ES), whereas male players had more recovery activities (small ES). During ball possession, male players spent a larger amount of time performing LIA (small ES) than female players, who displayed both the greatest number of HIA and the highest percentage of playing time performed at high intensity (small ES). Overall, these findings suggest that basketball coaches should design sex-specific training sessions based on the specific match demands.